Exploring the Intersection of Profit and Social Responsibility: Analyzing Unilever's Approach to Sustainable Business Practices - Nurhidayah, Fadila; Nur Setyaningtyas, Faridah; Ajra Syakira, Nafila (CV. Lafadz Jaya, 2025)
In the modern business era, companies face the challenge of balancing profit generation with social and environmental responsibility. This paper explores how Unilever, a global leader in consumer goods, successfully integrates both concepts through its Sustainable Living Plan (USLP). The USLP, launched in 2010, aims to improve health and well-being for over 1 billion people, reduce environmental impact by half, and enhance livelihoods across its supply chain. This study employs a content analysis methodology, reviewing 42 scholarly journals, articles, and relevant sources to examine Unilever's approach to balancing profit and purpose. Findings show that the USLP has enabled Unilever to achieve financial growth while also fostering positive social and environmental outcomes. The paper argues that integrating social responsibility into business strategies can provide long-term competitive advantages, strengthen brand reputation, and attract both consumers and investors concerned with sustainability. This case study of Unilever serves as a model for other companies looking to align profitability with societal impact, demonstrating that sustainability is not only a moral obligation but also a strategic business advantage.